PENEGAKAN HUKUM TERHADAP PENYALAHGUNAAN MINUMAN OPLOSAN BERALKOHOL GOLONGAN C OLEH REMAJA DAN ANCAMAN HUKUM BAGI PENJUAL TANPA IZIN DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA PEKANBARU - Kevin Pardede; Mukhlis R; Tengku Arif Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Mixed liquor is liquor made from various ingredients that contain alcoholand are mixed together, and have varying levels of alcohol. Selling bootlegalcohol, especially class C, illegally is an act that is against the law because itsells goods that endanger life and health, especially to teenagers who are stillunderage. Various efforts have been made by law enforcers, but the reality is thatthe perpetrators of the distribution of bootleg liquor so far in the Pekanbaru areacontinue to occur. Based on these problems, the authors are interested inknowing, first, how to enforce the law against the abuse of class C alcoholicmixed drinks by teenagers and legal threats to unlicensed sellers in thejurisdiction of the Pekanbaru city resort police, second, what obstacles are facedand efforts to overcome obstacles in law enforcement against abuse of class Calcoholic mixed drinks by teenagers and legal threats to unlicensed sellers in thejurisdiction of the Pekanbaru city resort police.This type of research is classified as sociological legal research. Innormative legal research, the data sources are primary data sources andsecondary data sources consisting of primary legal materials, secondary legalmaterials and tertiary legal materials. Collecting data on normative legalresearch uses data collection techniques by means of interviews and literaturestudies. The data obtained through a literature study will be analyzedqualitatively. In drawing conclusions the author uses the deductive thinkingmethod, namely a way of thinking that draws conclusions from a generalstatement or argument into a specific statement.Based on the results of the study it can be understood that law enforcementagainst the misuse of class C alcoholic mixed drinks by teenagers and legalthreats to unlicensed sellers in the jurisdiction of the Pekanbaru city resort policeis still weak, this can be seen that liquor is still freely sold and circulated tovarious groups in Pekanbaru city. Based on this, the constraints and efforts of thePekanbaru city resort police to supervise and socialize the adultery anddistribution of liquor. In this case, the perpetrators of the crime of mixing anddistributing liquor are subject to Article 204 of the Criminal Code, theperpetrators are subject to 15 years in prison.Keywords: Law Enforcement - Mixed Liquor - Pekanbaru City